Effects of Ammonia Flow Rate on the Synthesis of AIGaN Thin Films prepared via Spin Coating Approach - lsa, Nurul Atikah Mohd; Sha, Shiong Ng; Hassan, Zainuriah (2016)
We report on the growth or th e aluminum gallium nitride (A IGaN) thin film s on aluminum nitride (AIN) on silicon (Ill) tem plate via sol- gel spin coating method followed by nitridation process. The nitridation process was carried out for 75 min unlk r ammonia (NH3) ambient. To investigate the effects of NHJ flow rate on synthesis film , different NI-h flow rates (i .e., 200 seem, 300 seem and 400 seem) were used. The structural properties and surface morpho logies of the deposited films were accessed us ing X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM). The XRD results reveal that a ll the deposited AIGaN thin film s have wurtzite structure with the preferred growth orientation along the (002) crystallographic direction. As the N HJ tlow rate increases. the intensity of(002) peaks and crystal line quality were improved. The FESEM and AFM results show that the deposited AIGaN thin film have uniform and smooth surface. The optical properties of AIGaN thin film s were investigated by us ing Fourier transform infrared (FTIR) spectroscopy under the reflectance mode. The infrared reflectance results show that the intensity of E1(TO) peaks of the AIGaN increases with increasing NH3 flow rate. All the results reveal that the NHJ flow rate has significant effects on the structural surface morphologies and optical properties of the deposited film s. Finally. these results lead to conclude that the optimum NI-b flow rate is 400 seem.